2021
DOI: 10.1093/jxb/erab060
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fertilization induces nectar secretion for honeybee visitation and cross-pollination of almond trees

Abstract: Precise phosphorus (P) application requires a mechanistic understanding of mineral effects on crops' biology and physiology. Photosynthates assimilation, metabolism, and transport require phosphorylation, and we postulated that P is critical for the bloom and fruit-set of almond trees that rely on stored carbohydrate reserves. Hence, we studied the growth-physiology and carbohydrate dynamics in two-year-old almond trees irrigated with P concentrations between 1 and 20 mg L -1. Almond trees attained maximal pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Two microliters of treated nectar was applied to each flower, and after 2 days of exposure to pollinators, flowers were carefully removed along with the pedicel and placed in individual 1.5 ml microcentrifuge tubes containing 0.5 ml of water. This treatment volume approximates that of 24 h, per flower nectar production in Nonpareil (Abrol, 1995), as well as falls within the range of production volumes observed for related cultivars (Abrol, 1995; Karunakaran et al, 2021). Flowers were positioned such that the stigma did not touch the tube's surface and the pedicle was in water (Brittain et al, 2013).…”
Section: Methodssupporting
confidence: 76%
“…Two microliters of treated nectar was applied to each flower, and after 2 days of exposure to pollinators, flowers were carefully removed along with the pedicel and placed in individual 1.5 ml microcentrifuge tubes containing 0.5 ml of water. This treatment volume approximates that of 24 h, per flower nectar production in Nonpareil (Abrol, 1995), as well as falls within the range of production volumes observed for related cultivars (Abrol, 1995; Karunakaran et al, 2021). Flowers were positioned such that the stigma did not touch the tube's surface and the pedicle was in water (Brittain et al, 2013).…”
Section: Methodssupporting
confidence: 76%
“…The results suggest that pollinator visitation can be used as an indicator for precise P application to maximize yield and P use e ciency in a pollinatordependent species such as almonds. As a consequence, P fertilization affects sink activity and quality attributes of owers affecting fruit set as has been observed in olive (Erel et al 2016) and almond (Karunakaran et al 2021)trees, as it also seems to occurs in tomato.…”
Section: Discussionmentioning
confidence: 73%
“…4c), which could be due to the metabolic changes provoked, nonvisually observed but detected by the insects. Recently, it has been reported that P fertilization can improve almond yield by promoting pollinator (honeybees) visitation through mobilizing starch reserves and producing extra nectar (Karunakaran et al 2021). The results suggest that pollinator visitation can be used as an indicator for precise P application to maximize yield and P use e ciency in a pollinatordependent species such as almonds.…”
Section: Discussionmentioning
confidence: 99%